Cyclic Stress-Strain Behavior—Analysis, Experimentation, and Failure Prediction 1971
DOI: 10.1520/stp38029s
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Finite Element Stress Analysis and Stress-Strain Properties in Determining Notch Fatigue Specimen Deformation and Life

Abstract: Finite element elastic-plastic stress analyses were performed on several notched fatigue specimen geometries used in a test program to determine the room temperature and 550 F fatigue strengths of three low strength steels. Specimen geometries included grooved cylinders and wide notched cantilever bend specimens. The analyses were, with one exception, for reversed loading. The objective in these cases was to predict the steady state response of the specimens by using the cyclic stress-strain relationships. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Die Nennspannung ist sinngemäß definiert, wenn eine gemittelte konstante Spannung im Kerbquerschnitt gewählt wird, die die Gleichgewichtsbedingung erfüllt. Eine weitere Möglichkeit der Bestimmung der elastisch-plastischen Kerbbeanspruchung, besonders in unübersichtlichen Fällen, ist durch die Finite-Elemente-Methode gegeben [658]. Wenn die Spannungs-Dehnungs-Kurve nach Anpassung an die Fließspannung r 0Y2 den weiteren Verfestigungsverlauf nur unzureichend wiedergibt oder wenn der vollplastische Zustand miterfaßt werden soll, bieten sich genauere Näherungsformeln an, deren Grundstruktur theoretisch begründet ist, die jedoch über zunächst offene Parameter Spielraum für die Anpassung an die Gegebenheiten des Einzelfalls bieten.…”
Section: Makrostützwirkungsformel Nach Neuberunclassified
“…Die Nennspannung ist sinngemäß definiert, wenn eine gemittelte konstante Spannung im Kerbquerschnitt gewählt wird, die die Gleichgewichtsbedingung erfüllt. Eine weitere Möglichkeit der Bestimmung der elastisch-plastischen Kerbbeanspruchung, besonders in unübersichtlichen Fällen, ist durch die Finite-Elemente-Methode gegeben [658]. Wenn die Spannungs-Dehnungs-Kurve nach Anpassung an die Fließspannung r 0Y2 den weiteren Verfestigungsverlauf nur unzureichend wiedergibt oder wenn der vollplastische Zustand miterfaßt werden soll, bieten sich genauere Näherungsformeln an, deren Grundstruktur theoretisch begründet ist, die jedoch über zunächst offene Parameter Spielraum für die Anpassung an die Gegebenheiten des Einzelfalls bieten.…”
Section: Makrostützwirkungsformel Nach Neuberunclassified
“…As discussed earlier, Neuber's rule may overestimate the notch root strains under multiaxial stress state conditions, while it seems to provide more reliable results for plane stress conditions. A comparison of the analytical approximations with the FE analysis showed that the Neuber method and the SED criterion provide almost identical results, which are conservative compared to the results of the FE model and, hence, may be better used as first estimations [9]. However, the underestimation of notch root strains by quite large margins was also reported elsewhere [9].…”
Section: Analytical Results With Ls Approachmentioning
confidence: 77%
“…They suggested that estimations using the SED criterion and Neuber' s rule will give lower and upper limits on the local strain, which can be used to bound an uncertainty field for the life prediction. When yielding at the notch takes place, more accurate results of the local notch response may be obtained with an finite element analysis (FEA) [9].…”
Section: Introductionmentioning
confidence: 99%
“…If in reversal 5 , AS5 is +25 instead of +50, the load and the nominal stress will be zero. We may find the residual stress upon unloading by using equations (8) and (9) In general, whenever the residual stress and strain are wanted, make the load or nominal stress equal to zero by adding a load reversal AS,. Since this is an elastic reversal, equations (8) and (9) A summary of results is given in Figure 9 and Table 111.…”
Section: Residual Stress and Strainmentioning
confidence: 99%